If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + -6 = 8a + 1 Reorder the terms: -6 + 9a = 8a + 1 Reorder the terms: -6 + 9a = 1 + 8a Solving -6 + 9a = 1 + 8a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8a' to each side of the equation. -6 + 9a + -8a = 1 + 8a + -8a Combine like terms: 9a + -8a = 1a -6 + 1a = 1 + 8a + -8a Combine like terms: 8a + -8a = 0 -6 + 1a = 1 + 0 -6 + 1a = 1 Add '6' to each side of the equation. -6 + 6 + 1a = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 1a = 1 + 6 1a = 1 + 6 Combine like terms: 1 + 6 = 7 1a = 7 Divide each side by '1'. a = 7 Simplifying a = 7
| 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) | | 16a^4+36a^3b-10a^2b^2= | | 5(7n-4)-3= | | -0.666+4w=-0.111 | | -7+4(1+5a)= | | 9xa+1=8a | | 2v^2(8v^2+6vb-5b^2)= | | (z^4/16)^3/4 | | (m-3)+5=16 | | 2(10x-3)-4x= | | x^2-8x+132=120 | | 5(7+6m)-10= | | 24(y-1)=-6(5+y) | | -4b+3(b+5)= | | -(v+3)-5= | | Yk+yq=k | | 4-sqrt8/sqrtx-6 |